DEVELOPMENT OF GOOGLE SITES-BASED E-LEARNING TO ENHANCE READING COMPREHENSION SKILLS OF NARRATIVE TEXTS FOR 5TH GRADE ELEMENTARY SCHOOL STUDENTS - Tri Widyaswari; Sardianto Markos Siahaan; Deris Stiawan (University of Kuningan, 2026)
The development of digital technology necessitates the availability of interactive, flexible learning media that can enhance student engagement in the learning process. This study aims to analyze the effectiveness of Google Sites-based e-learning media in improving the reading comprehension skills of narrative texts among 8th-grade students. The research method employed a quasi-experimental design with a pretest-posttest control group model, involving 48 participants, consisting of an experimental class and a control class. The research instruments included a reading comprehension test, observation sheets, and student response questionnaires. The results showed that the web-based learning media significantly improved students' reading comprehension skills, as indicated by an average N-Gain of 0.77 (high category) in the experimental class, which was superior to the control class with an N-Gain of 0.47 (moderate category). Additionally, students showed very positive responses to the media's appearance, interactivity, and ease of access. These findings confirm that the integration of web-based digital media can support self-directed learning, increase multimodal engagement, and strengthen the text comprehension process. Therefore, Google Sites proves to be an effective modern learning media that can be implemented in language learning, particularly in enhancing reading comprehension skills.